Direito ao esquecimento e direito à memória e à verdade: uma análise sobre o posicionamento do Superior Tribunal de Justiça nos casos “familiares de Amelinha Teles versus USTRA” e “Zarattini versus Diário de Pernambuco”. - Oliveira, Nara Fonseca de Santa Cruz (2024)
This thesis aims to investigate whether the way the Superior Court of Justice (STJ) has been interpreting and recognizing the so-called right to be forgotten might undermine the right to memory and truth, as well as the still precarious and incomplete Brazilian transitional justice process. It is noted that although the debate on the so-called right to be forgotten is not new, with decisions dating back to the last century, the discussion has been expanded with the advancement of new technologies, particularly the internet, which is not subject to the common biological process of forgetting. This research brought to light emblematic cases on the topic, including international cases, as current debates are profoundly influenced by these precedents. Additionally, the study addressed the right to memory and truth, highlighting the 1979 Amnesty Law, considered the foundational landmark of the Brazilian transitional process. The constitutional resistance thesis developed by Eneá de Stutz, based on the philosopher François Ost, was explored. Stutz argues for the existence of two types of political amnesty: amnesty of the facts (greater amnesty) and amnesty of penalties or convictions (lesser amnesty). In contrast to the hegemonic conception, it is argued that Brazilian political amnesty referred to convictions, preserving memory rather than erasing facts. As demonstrated, legal frameworks on transitional justice, including the Amnesty Law, have privileged memory (anamnese) over forgetting (amnésia). To assess whether the STJ's interpretation of the right to be forgotten could threaten the right to memory and truth, a search was conducted on the STJ website using the keywords “right to be forgotten,” focusing on cases where this right is recognized as a type of personality right, similar to image and honor. Of the 85 cases filtered, only 14 were relevant to this thesis. The analysis of these decisions revealed 2 cases where the right to be forgotten was mistakenly associated with the Amnesty Law: the cases “Zarattini vs. Diário de Pernambuco” and “Family Members of Amelinha Teles vs. Ustra.” Both cases are central to this research, as they involve the conflict between the right to be forgotten and the right to memory and truth. The STJ's positions in Special Appeals No. 1.369.571/PE (case “Ricardo Zarattini vs. Diário de Pernambuco”) and No. 1.434.498/SP (case “Family Members of Amelinha Teles vs. Ustra”) were critically analyzed in light of Stutz's constitutional resistance thesis, identifying potential risks to the preservation of memory and the establishment of truth. It was observed that the STJ interpreted the right to be forgotten as deriving from the Amnesty Law, based on the hegemonic conception that amnesty always equates to forgetting. This study argues that the right to memory and truth should serve as a limit to the application of the right to be forgotten. In other words, in cases of conflict between the so-called right to be forgotten and the right to memory and truth, the latter should prevail, as political amnesty advocated the preservation of memory.